Dual dynamic airflow protection for the removal of fused silica micron particles in the final optics assembly. Issue 3 (3rd March 2020) - Peng, Ge; Chen, Jiaxuan; Lu, Lihua; Miao, Xinxiang; Dong, Zhe; Leng, Daming
Abstract: Micron-sized particles generated during laser-induced event are difficult to control in large optical systems such as final optics assembly (FOA) and have a great impact on load capacity. The related removal methods of these particles have become concerns. This study investigated a latest removal method of dual dynamic airflow protection for micron particles of diameters from 0.5 to 50 μm by laser-induced fused silica in the FOA. Firstly, a device for obstructing longitudinal movement of particles was established, which adopted the vertical "air curtain" coupled with laminar background flow to realize the first step to weaken threat of small diameter particles (0.5–5 μm). Next, numerical simulations of coupled field in the neutral plane was applied to help analyze the whole protective process and the dynamic removal mechanisms. Secondly, individual air knives were locally installed on the top of each optics to form high speed films as a secondary protection to avoid large-diameter particles (5–50 μm, with different initial velocities which could break through the curtain) from landing onto the surfaces. By statistically comparing the results, we found that the dual dynamic protection methods mixed with laminar flow and air knives in various arrangement could basically achieve the goal of pre-protection and removal of laser-induced micron particles of fused silica to maintain high cleanliness levels of optics surface. Copyright © 2019 American Association for Aerosol Research